Who Wrote This? Detecting Artificial Intelligence–Generated Text from Human-Written Text - Kumar, Rahul; Mindzak, Michael (Canadian Perspectives on Academic Integrity, 2024)
This article explores the impact of artificial intelligence (AI) on written compositions in education. The study examines participants’ accuracy in distinguishing between texts generated by humans and those produced by generative AI (GenAI). The study challenges the assumption that the listed author of a paper is the one who wrote it, which has implications for formal educational systems. If GenAI text becomes indistinguishable from human-generated text to a human instructor, marker, or grader, it raises concerns about the authenticity of submitted work. This is particularly relevant in post-secondary education, where academic papers are crucial in assessing students’ learning, application, and reflection. The study had 135 participants who were randomly presented with two passages in one session. The passages were on the topic of “How will technology change education?” and were placed into one of three pools based on the source of origin: written by researchers, generated by AI, and searched and copied from the internet. The study found that participants were able to identify human-generated texts with an accuracy rate of 63%. But with an accuracy of only 24% when the composition was AI-generated. However, the study also had limitations, such as limited sample size and an older predecessor of the current GenAI software. Overall, this study highlights the potential impact of AI on education and the need for further research to evaluate comparisons between AI-generated and human-generated text.